Ultrasound evaluation of the placenta in healthy and placental syndrome pregnancies: A systematic review. (July 2021) - Schiffer, Veronique; van Haren, Ashlee; De Cubber, Lisa; Bons, Judith; Coumans, Audrey; van Kuijk, Sander MJ; Spaanderman, Marc; Al-Nasiry, Salwan
Abstract: Introduction: An antepartum screening method to determine normal and abnormal placental function is desirable in the prevention of maternal and fetal pregnancy complications. Placental appearance can easily be obtained and evaluated using 2D ultrasonography, but surprisingly little is known about the change in placental appearance during gestation. Aim of this systematic review was to describe the antepartum placental appearance in placenta syndrome (PS) pregnancies, and to compare this to the appearance in healthy pregnancies. Methods: A systematic review investigating placental thickness, -lakes and/or -calcifications by ultrasound examination in both uncomplicated (reference group) and PS pregnancies in relation to gestational age was performed. English literature was searched using PubMed (NCBI), EMBASE (Ovid) and the Cochrane Library, from database inception until September 2020. Data on placental thickness was presented as a continuous variable or as the proportion of abnormal placental thickness. Data on placental lakes and -calcifications was presented as prevalence (%). There was no restriction applied on the definition of placental lakes or -calcifications. Due to heterogeneity, pooling of the results was not performed. Results: A total of 28 studies were included describing 1719 PS cases; consisting of 370 (21 %) cases with preeclampsia or pregnancy induced hypertension, 1341 (78 %) cases with fetal growth restriction (FGR) or small for gestational age (SGA), and 8 (1%) cases with combined clinical expressions. In addition, the reference group comprised 3315 pregnant women. Placental thickness showed an increase between the first and second trimester, which was higher in PS- compared to uncomplicated pregnancies. Placental lakes were frequently observed in FGR and SGA pregnancies, especially in the second trimester. Grade 3 calcifications were most prominent in the PS pregnancies, specifically in the late second and third trimester. Moreover, in the reference group, no grade 3 calcifications were reported before 35 weeks of gestation. Conclusion: Placental appearance in PS-pregnancies shows higher placental thickness and greater presence of placental lakes and –calcifications compared to uncomplicated pregnancies. Standardized definitions of (ab-)normal placental appearance and longitudinal research in both healthy and complicated pregnancies are needed to improve personalized obstetric care.